(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Obesity is a chronic disease defined by an excessive accumulation of body fat that represents health risks, being considered now a days the major public health problem worldwide. Obesity is characterized as a low-grade inflammatory disease due to the variety of pro-inflammatory adipokines secreted by adipose tissue, especially visceral adipose tissue. This inflammation is characterized by macrophage infiltration and expression of inflammatory adipokines, which are related to insulin resistance, blood pressure, and vascular endothelium alterations. These alterations are closely related to development and progression of diabetes and cardiovascular disease, including paediatric patients. Obesity considered now as one among the major global issue affecting young adults. Rapid changes in sedentary lifestyle choices were the risk factors for obesity including unhealthy diet patterns, expending time in front of TV and lacking physical activity etc. The present study aimed for correlating the risk factors of obesity with healthy groups among the adolescent population. And the result was recorded with significant level of elevation in most of the parameters in cases than control and the significance was represented as student’s test (p<0.001).